1974
DOI: 10.1037/h0037417
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and the three-function learning: Food deprivation and approach-avoidance to food words.

Abstract: Food words were considered as conditioned stimuli that elicit an appetitive emotional response. The emotional response-according to the two-process, three-stimulus-function learning theory involved-should be capable of mediating instrumental behavior toward the words. Motivational principles elaborated in the context of the three-function theory predicted that 5s deprived of food would learn to respond more quickly with an approach instrumental response to food words than would deprived 5s whose task was to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Humans are faster to perform a response that makes a positively-valenced word approach rather than recede (Solarz, 1960), a tendency that is modulated by hunger in the case of food-related words (Staats and Warren, 1974). Moreover, pavlovian-instrumental transfer procedures demonstrate that an appetitive CS augments human performance of an instrumental response (Hogarth et al, 2007;Bray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Humans are faster to perform a response that makes a positively-valenced word approach rather than recede (Solarz, 1960), a tendency that is modulated by hunger in the case of food-related words (Staats and Warren, 1974). Moreover, pavlovian-instrumental transfer procedures demonstrate that an appetitive CS augments human performance of an instrumental response (Hogarth et al, 2007;Bray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 2 was conducted, in part , to elucidate the role of the FCAR mediation in an appetitive transfer experiment. Staats and Warren (1974) stated that transfer would not occur if the animals had not previously learned to barpress for food: Without that training, the mediational associations between the mediator and the barpressing would not be formed. (They discussed an emotionresponse mediator, but the same would pertain to the FCAR mediation.)…”
Section: Resultsmentioning
confidence: 99%
“…In beginning the analysis of transfer of control within the framework of the three-function learning theory of social behaviorism (see Staats, 1975), the purpose of Experiment 1 was to validate the transfer phenomenon by replicating the prototypical appetitive transfer experiment. Previous social behaviorism research has shown the importance of analyzing the stimuli and responses in experimental situations (Staats, 1964).…”
mentioning
confidence: 99%
“…Staats, Minke, Martin, and Higa (1972) showed the food words could transfer the conditioned emotional response to a neutral stimulus, in a classical conditioning procedure, more strongly for food-deprived subjects than for nondeprived subjects. Staats and Warren (1974) showed that fooddeprived subjects could learn an approach response to food words as the directive (discrim inative) stimulus in a two-choice response task more rapidly than they could learn an avoidance response, and that such subjects learned an approach response to food words more rapidly than did nondeprived subjects.…”
Section: University Ofhawaii Honolulu Hawaii 96822mentioning
confidence: 99%
“…This three-function theory has also indicated that in the mature organism, through learning, a stimulus that is a es for an emotional response and hence can be a reinforcing stimulus will also function as a directive (discriminative) stimulus and control either approach instrumental responses (in the positive case) or avoidance responses (in the negative case) (Staats, 1975). There are a number of studies on the animal level (e.g., Brown & Jenkins, 1968;Trapold & Winokur, 1967;Zimmerman, 1957) that can be interpreted and integrated with the three-function learning theory (Staats, 1975;Staats & Warren, 1974), as well as a number of studies on the human level (Staats, 1975).…”
Section: University Ofhawaii Honolulu Hawaii 96822mentioning
confidence: 99%